The Role of Islamic Religious Education Teachers in Improving the Morals of Middle School Students - Tahir, Muhyiddin; Muhsyanur, Muhsyanur; Alfina, Alfina (ETDC: Indonesian Journal of Research and Educational Review, 2022)
This article discusses the role of islamic religious education teachers in improving the morals of students at satap lambuya middle school, konawe regency, southeast sulawesi province with the main problems being (1) How is the learning of Islamic Religious Education teachers in improving the morals of students at Satap Lambuya Junior High School, Konawe regency, southeast sulawesi province? (2) How to improve the morals of students at SMP Satap Lambuya, Konawe Regency, Southeast Sulawesi Province? (3) What is the role of Islamic Religious Education teachers in improving the morals of students at SMP Satap Lambuya, Konawe Regency, Southeast Sulawesi Province? This type of research is qualitative. The location of this research is students at satap lambuya middle school, konawe regency, southeast sulawesi. The approach used is an ethnomethodological study, with data collection methods, namely observation, interviews and documentation. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions and data verification. The results of the research show that Islamic religious education teachers should not only make all educational plans listed in the curriculum and learning units as the only estuary in achieving educational goals, learners are always a problem and as a focus of attention, a teacher is needed who can direct the behavior of students to achieve their learning goals, and In order to implement the Islamic Religious Education Teacher Program which has been mandated in the Vision and Mission, the role of activities carried out by Islamic religious teachers to be pioneers in implementing the moral values of students must be programmed properly and must be implemented optimally.